Exploring the psychology of teachers' learner-centered beliefs and classroom practices - Alcantara, Ma. Cynthia A. (2007)
Ongoing controversy about how to prepare teachers has placed new urgency on studies of teaching experience. This study presented an attempt to explore how the concept of learner-centeredness is operationalized in the secondary schools, particularly in an exclusive girls' high school in Quezon City, which espouses this in its Mission statement. An ex post facto correlational research design utilizing a two-phase sequential mixed methods procedure was employed to complete the study. The Assessment of Learner-Centered Practices (ACLP) Survey for teachers and students, developed by McCombs (1999) were used. Results showed that the teachers expressed agreement both to learner-centered and non learner-centered beliefs. It likewise revealed the effect of the years of teaching experience in the institution to the students' perception of the learner-centered practices but not to the teachers' demonstration of these practices.